Study of extrapulmonary tuberculosis in tertiary care hospital children with reference to cartridge based nucleic acid amplification test - Shah, Chirag; Jain, Shantanu; Patel, Pathik (International Journal of Contemporary Pediatrics, 2021)
Background: Tuberculosis is an infectious disease cause by the mycobacterium tuberculosis which typically involve lung but can affect other site called extrapulmonary tuberculosis (EPTB). In EPTB lymph node tuberculosis is most common and most severe is tuberculous meningitis. Cartridge based nucleic acid amplification test (CBNAAT) have high sensitivity and perform both respiratory and non-respiratory specimen. The aim of this retrospective study is to find out the proportion of extra pulmonary tuberculosis in hospitalized patient and determine the association of CBNAAT in diagnosis EPTB and Rifampicin resistance. Methods: This is the retrospective observational study done at Civil Hospital Ahmedabad in between October 2017 to October 2019 among the admitted patient age 1 month to 12 year diagnosed cases of EPTB according to RNTCP guidelines. Data collection done by medical records as indoor case sheets and investigation data from laboratory department. Results: Incidence of EPTB among the hospitalized children is 1.95% and among total tuberculosis patient is 42.48%. Among 191 suspected EPTB cases 59 confirmed indicate sensitivity of 37.3% and no false positive cases indicate 100% positive predictive value. Sensitivity of CBNAAT was highest in gastric aspirate followed by CSF in present study. Conclusions: Tuberculosis is more common in male child less than 5-year-old with frequent risk factor is rural residential area, lower socioeconomic class and contact with active cases. In my study is CNS tuberculosis is most common. In my study mortality is higher among 1-to-5-year age group with co morbid condition are SAM and septicemia.